IN- VIVO ANTIOXIDANT RELATED EFFECTS OF ORALLY ADMINISTERED AQUEOUS EXTRACT OF LEMON BALM (MELISSA OFFICINALIS L.) IN HUMAN - NESSRIN GHAZI ALABDALLAT (International Journal of Pharma and Bio Sciences, 2016)
emon balm (Melissa officinalis L.), belongs to the family Lamiaceae (Labiatae), is one of the important medicinal plant species. The present work aimed to investigate antioxidant related effects of Lemon balm in humans by in vivo study & effects on liver, renal & cardiac function tests. Nine healthy volunteers, each received orally 250 ml of aqueous extract of Lemon balm daily for 5 days. Venous bloods were taken before and one hour after the first dose of aqueous extract (sample I and II respectively) and then one day after the last dose of day five (i.e. day 6, sample III). The first blood taken before the first dose (i.e. sample I), served as control for the next samples of II and III. The following assays were performed: serum total antioxidant status (TAS), erythrocyte reduced glutathione (GSH), malonyldialdehyde (MDA), and serum selected biochemical tests. Oral administration of aqueous extracts of Lemon balm to healthy volunteers, for 5 days, increased significantly serum TAS, erythrocyte GSH and decreased significantly erythrocyte MDA, with no effect on serum biochemical tests for kidney, liver, cardiac and pancreatic, compared to 0 time administration. In conclusion: Lemon balm extract has efficient in vivo antioxidant related effects. As the present findings are obtained in healthy humans with no oxidative stress, this indicates that Lemon balm can improve the base line of the defense mechanisms against possible oxidative stress, with no adverse effects, thus decreasing susceptibility or preventing the progress of pathological conditions related to oxidative stress.